Photojournalisme contemporain : les enjeux de la conservation patrimoniale d’une mémoire collective - Frédérique Gaillard (In Situ)
The heritage conservation of contemporary photojournalism raises many questions and its challenges are numerous. In a few decades, an important visual heritage has been created. The sheer numbers of photographs and of photographers make conservation complex, involving issues such as the costs of digitisation, conservation material, data backup on servers, copyright, contextualisation of pictures… Many photographers are worried about the future of their collections and are looking for the best ways to preserve them. Several strategies are to be observed: donation to archive centres, creation of associations or foundations. In the Occitanie region, two local authorities have recently made their mark in photographic projects. The city of Toulouse has worked for more than ten years on the acquisition of the important photo collection of Jean Dieuzaide. The city of Perpignan has created an international centre for photojournalism to preserve and interpret photographic collections. The interest of the conservation of these photographs is studied through their various aspects, bringing to bear different approaches in contemporary history, sociology, information and communication sciences, anthropology and visual anthropology… Many photographic reportages have emerged as historical time markers and contribute to shaping our collective memory. Efforts to take this collective memory aspect into consideration make it even more difficult to understand the pictures and the issues they raise.